2011
DOI: 10.1007/s10661-011-1925-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, aboveground biomass, and nutrient concentration of young Scots pine and lodgepole pine in oil shale post-mining landscapes in Estonia

Abstract: The investigation was carried out in 8-year-old Scots pine (Pinus sylvestris L.) and lodgepole pine (Pinus contorta var. latifolia Engelm.) plantations on post-mining area, Northeast Estonia. The aim of the study was to assess the suitability of lodgepole pine for restoration of degraded lands by comparing the growth, biomass, and nutrient concentration of studied species. The height growth of trees was greater in the Scots pine stand, but the tree aboveground biomass was slightly larger in the lodgepole pine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The branches, foliage, and fruits in their study accounted 11, 13, and 4 percent of total aboveground biomass respectively. However, Kuznetsova et al (2011) found only 31 and 27 percent of aboveground biomass in the main stem of 8-year old Scots pine and lodgepole pine respectively in the oil shale postmining landscapes in Estonia. They found 32 and 28 percent in shoots and 37 and 45 percent in the needles of those 8-year old scots pine and lodgepole pine respectively.…”
Section: R a F Tmentioning
confidence: 87%
“…The branches, foliage, and fruits in their study accounted 11, 13, and 4 percent of total aboveground biomass respectively. However, Kuznetsova et al (2011) found only 31 and 27 percent of aboveground biomass in the main stem of 8-year old Scots pine and lodgepole pine respectively in the oil shale postmining landscapes in Estonia. They found 32 and 28 percent in shoots and 37 and 45 percent in the needles of those 8-year old scots pine and lodgepole pine respectively.…”
Section: R a F Tmentioning
confidence: 87%
“…No big differences in biomass fractions were found between species, but differences in biomass production and component analysis were observed, confirming our hypothesis that biomass production would be dissimilar between species. Kuznetsova et al (2011) also found differences between species in terms of growth and biomass allocation when analyzing aboveground biomass of eight-year-old Pinus sylvestris and Pinus contorta trees in Estonia. In the present work, the effect of density varied between species and was significant for Pinus halepensis but not significant for Pinus pinaster.…”
Section: Discussionmentioning
confidence: 82%
“…The effectiveness of nitrogen was previously discussed by Norgren & Elfving (1994), Norgren (1996) and Kuznetsova et al (2011). As stated in the earlier studies, the size of the needles is restricted by their ability to access nitrogen (Norgren & Elfving 1994).…”
Section: Nutrient Allocationmentioning
confidence: 91%